A Novel ARTP-derived Bacillus megaterium Mutant with Enhanced Salt Tolerance and Plant Growth Promotion in Saline–alkali Soil - Min Sun; PengFei Qiu; XinJie Yuan; QiLi Zhu; ZhenXing Peng; JiMin Lv; HongShun Li; JunPing Bao; YanQing Wei; ShuDong Qu; XianShun Ren; ZiHao Wang; et al. (Current Microbiology, 2026)
Soil salinization seriously threatens global food security with continuously expanding affected areas. Bacillus megaterium -based bioinoculant serves as an eco-friendly strategy for saline–alkali land remediation, whereas wild-type (WT) strains generally exhibit poor salt–alkali tolerance. To address this limitation, atmospheric and room temperature plasma (ARTP) mutagenesis combined with a microbial microdroplet culture (MMC) high-throughput screening system was adopted to screen high salt-tolerant B. megaterium mutant followed by multi-omics characterization. Using WT B. megaterium LD (CGMCC No.21828) as the original strain, a mutant library was constructed via optimized ARTP treatment, and the elite mutant SLD48 was isolated under dynamically increasing salt gradients. Compared with the wild type, SLD48 possesses a larger genome of 6,252,538 bp and acquires 28 extra functional genes including spoIVCA and pJ_gene0003 . Intracellular osmoprotectants (proline, glycine betaine) and antioxidant α-tocopherol were markedly accumulated in SLD48. moreover, exogenous supplementation of these substances in the culture medium can effectively alleviate the damage caused by salt stress to the cells. In pot trials with saline–alkali soil, the rhizosphere colonization of SLD48 reached 3.52 × 10⁵ CFU/g (2.46-fold of LD), and maize shoot fresh weight increased by 40.5% after inoculation. Collectively, this work confirms that mutant SLD48 is a promising microbial resource for saline–alkali soil improvement and crop yield promotion.

Molecular disruption of neuroinflammatory and metabolic pathways mediates triclosan-induced depressive-like behavior in zebrafish - Danting Wang; Junping Liu; Ruixue Zhou; Bing Han; Chunxia Chen; Wentong Meng; Li Qin; Limei Sun; Bin Tan; Chunyan Huang (Toxicology and Applied Pharmacology, 2026)

ZIP14-VDAC2 mediates the transport of extracellular iron into mitochondria in hepatocytes under PFOS exposure - Yu Li; Min Yu; Junping Ren; Tianming Qiu; Jingyuan Zhang; Chenbing Wu; Jie Bai; Xiance Sun; Xiaofeng Yao (Chemico-Biological Interactions, 2026)

Precipitation patterns of nitrogen and phosphorus in reservoirs: A study in typical sand-source area of Inner Mongolia using PMF-HYSPLIT model - Zhuo Li; Junping Lu; Tingxi Liu; Yi Wang; Jiahui Mi; Zhenyu Shi; Chen Feng; Yinghui Liu; Aojie Sun (Journal of Environmental Sciences, 2025)

Characteristics of nitrogen and phosphorus migration at sediment-water interface in seasonal frozen lakes and the mechanism of microbial driven cycling: a case study of Lake Daihai - Rong Wu; Xiaohong Shi; Xueer Kang; Sheng Zhang; Shengnan Zhao; Yu Liu; Biao Sun; Junping Lu; Haifeng Yu; Shihuan Wang; Xueru Pan; Kaiqi Shen; et al. (Journal of Contaminant Hydrology, 2025)

Silibinin alleviates acute liver failure by modulating AKT/GSK3β/Nrf2/GPX4 pathway - Yue Li; Hailan Li; Minhui Sun; Hong Chen; Yao Xiao; Jieman Wang; Yuanyuan Zhang; Shuhua Fang; Junping Kou (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Late Carboniferous to Permian paleoclimatic and tectono-sedimentary evolution of the central Ordos Basin, western north China Block - Hua Tao; Junping Cui; Jiaopeng Sun; Zhanli Ren; Fanfan Zhao; Shihao Su; Wei Guo; Haoyu Song (Marine and Petroleum Geology, 2025)

Removal of Cu2+ and Cd2+ by modified chitosan hydrogel - Heyu Sun; Junping Han; Chunyan Kong; Jiang Zhan; Li Chen; Yiping Zhao (Journal of Water Process Engineering, 2025)

Spatial distributions, potential sources, and ecological risks of heavy metals in stream sediments in Zambia - Hongwei Sun; Junping Ren; Jie Wang; Jianzhong Yu; Libo Zuo; Xingyuan Wu; Chipilauka Mukofu; Alphet Phaskani Dokowe; Shuping Cao; Xujiang Cheng (Journal of Geochemical Exploration, 2025)

Spatial pattern and methylation process of mercury enrichment in lake sediments during glacial periods in cold and arid regions - Jinda Zhang; Hui Zhang; Shengnan Zhao; Xiaohong Shi; Biao Sun; Junping Lu; Yu Liu; Wenbao Li; Yunxi Zhao; Zhimou Cui (Environmental Pollution, 2025)

Energy-locking-loop: Heterogeneous gel interphase potential enhances battery performance - Meizhi Li; Miao Sun; Guochen Ji; Junping Zheng (Chemical Engineering Journal, 2025)

Array shape calibration based on coherence of noise radiated by non-cooperative ships - Wenchang Zhang; Pengfei Jiang; Jianheng Lin; Junping Sun (Ocean Engineering, 2024)

A review of the geological characteristics and resource potential analysis of potash deposits in Africa - Hongwei Sun; Junping Ren; Jie Wang; Xingyuan Wu; Wenlong Tang (Journal of African Earth Sciences, 2024)

Scaffold protein BTB/TAZ domain-containing genes (CmBTs) play a negative role in root development of chrysanthemum - Lianda Du; Zhangji Guan; Yanhong Liu; Dagang Hu; Junping Gao; Cuihui Sun (Plant Science, 2024)

Development and performance evaluation of a culture-independent nanopore amplicon-based sequencing method for accurate typing and antimicrobial resistance profiling in Neisseria gonorrhoeae - Chi Zhang; Lulu Zhang; Feng Wang; Yaling Zeng; Liying Sun; Di Wang; Yamei Li; Liqin Wang; Junping Peng (Science China Life Sciences, 2024)

Characterization and traceability analysis of dry deposition of atmospheric microplastics (MPs) in Wuliangsuhai Lake - Kai Wang; Yu Liu; Xiaohong Shi; Shengnan Zhao; Biao Sun; Junping Lu; Wenbao Li (Science of The Total Environment, 2024)

Craniocervical Manual Lymphatic Drainage Increases the Efficiency of Atorvastatin-Based Treatment of Chronic Subdural Hematoma - Chuang Gao; Yingsheng Wei; Xinjie Zhang; Jinhao Huang; Meng Nie; Xuanhui Liu; Jiangyuan Yuan; Dong Wang; Ye Tian; Weiwei Jiang; Shuo An; Jian Sun; et al. (Translational Stroke Research, 2023)

Pore structure evolution of mudstone caprock under cyclic load-unload and its influence on breakthrough pressure - Junchang Sun; Zhiqiang Dong; Sinan Zhu; Shifeng Tian; Junping Zhou (Frontiers of Earth Science, 2023)

A hydrogel electrolyte with ultrahigh ionic conductivity and transference number benefit from Zn2+ “highways” for dendrite-free Zn-MnO2 battery - Miao Sun; Guochen Ji; Junping Zheng (Chemical Engineering Journal, 2023)

The spatial distribution and abundance of microplastics in lake waters and ice during ice-free and ice-covered periods - Yu Liu; Xiaohong Shi; Sheng Zhang; Junping Lu; Wenbao Li; Biao Sun; Shengnan Zhao; Dingwen Yao; Jussi Huotari (Environmental Pollution, 2023)

The influences of composition and pore structure on the adsorption behavior of CH4 and CO2 on shale - Xiangzeng Wang; Junping Zhou; Xiao Sun; Shifeng Tian; Jiren Tang; Feng Shen; Jinqiao Wu (Frontiers of Earth Science, 2021)

Chemical constituents from Ginkgo biloba leaves and their cytotoxicity activity - Penghua Shu; Mengyuan Sun; Junping Li; Lingxiang Zhang; Haichang Xu; Yueyue Lou; Zhiyu Ju; Xialan Wei; Wenming Wu; Na Sun (Journal of Natural Medicines, 2020)

Construction of a recombinant duck enteritis virus vaccine expressing hemagglutinin of H9N2 avian influenza virus and evaluation of its efficacy in ducks - Ying Sun; Chenghuai Yang; Junping Li; Ling Li; Minghui Cao; Qihong Li; Huijiao Li (Archives of Virology, 2017)

The Effect of Substrate Stiffness on Cardiomyocyte Action Potentials - Sean D. Boothe; Jackson D. Myers; Seokwon Pok; Junping Sun; Yutao Xi; Raymond M Nieto; Jie Cheng; Jeffrey G. Jacot (Cell Biochemistry and Biophysics, 2016)

Detection, discrimination and quantitation of 22 bluetongue virus serotypes using real-time RT-PCR with TaqMan MGB probes - Yufei Feng; Tao Yang; Qingyuan Xu; Encheng Sun; Junping Li; Shuang Lv; Haixiu Wang; Qin Zhang; Jikai Zhang; Donglai Wu (Archives of Virology, 2015)

Biological properties of a duck enteritis virus attenuated via serial passaging in chick embryo fibroblasts - Chenghuai Yang; Junping Li; Qihong Li; Ling Li; Miao Sun; Huijiao Li; Yecai Xia; Hanchun Yang; Kangzhen Yu (Archives of Virology, 2015)

Rapamycin promotes podocyte autophagy and ameliorates renal injury in diabetic mice - Tangli Xiao; Xu Guan; Ling Nie; Song Wang; Lei Sun; Ting He; Yunjian Huang; Jingbo Zhang; Ke Yang; Junping Wang; Jinghong Zhao (Molecular and Cellular Biochemistry, 2014)